Incremental value of myocardial perfusion over coronary angiography by spectral computed tomography in patients with intermediate to high likelihood of coronary artery disease - Carrascosa, Patricia M. (2015)
Purpose: We sought to explore the diagnostic performance of dual energy computed tomography (DECT) for the evaluation of myocardial perfusion in patients with intermediate to high likelihood of coronary artery disease (CAD). Materials and methods: Consecutive patients with known or suspected CAD referred for myocardial perfusion imaging by single-photon emission computed tomography (SPECT) constituted the study population and were scanned using a DECT scanner equipped with gemstone detectors for spectral imaging, and a SPECT. The same pharmacological stress was used for both scans. Results: Twenty-five patients were prospectively included in the study protocol. The mean age was 63.4 ± 10.6 years. The total mean effective radiation dose was 7.5 ± 1.2 mSv with DECT and 8.2 ± 1.7 mSv with SPECT (p = 0.007). A total of 425 left ventricular segments were evaluated by DECT, showing a reliable accuracy for the detection of reversible perfusion defects [area under ROC curve (AUC) 0.84 (0.80-0.87)]. Furthermore, adding stress myocardial perfusion provided a significant incremental value over anatomical evaluation alone by computed tomography coronary angiography [AUC 0.70 (0.65-0.74), p = 0.003]. Conclusions: In this pilot investigation, stress myocardial perfusion by DECT demonstrated a significant incremental value over anatomical evaluation alone by CTCA for the detection of reversible perfusion defects.